Pricing and package size decisions in crowdfunding. (November 2020) - Peng, Jing; Zhang, Jianghua; Nie, Tengfei; Zhu, Yangguang; Du, Shaofu
Highlights: Consider consumers' heterogeneity of usages and valuations in a crowdfunding mechanism. Identify the optimal pricing strategy and project target under exogenous package size. Providing different kinds of packages can benefit the creator compared with a single package. Derive the optimal joint decision in package size, pricing strategy and project target. Abstract: Pricing and package size decisions are critical to the success or failure of reward-based crowdfunding projects; the importance of these decisions has been overlooked in the existing crowdfunding literature. In this paper, we develop a two-period model to study pricing and package size decisions in a crowdfunding game where a creator sells perishable products to sequentially arriving consumers. Consumers are heterogeneous in their usages and valuations and they get utility by consuming products rather than owning them. The creator can choose to provide a product menu that contains two types of packages or only provide one type of package to match the consumers' usages and valuations. The project would succeed only when the project target is achieved during the funding period; otherwise, the transaction would be canceled. We show that consumers' usages and valuations have a large impact on deciding the creator's optimal pricing strategy and project target regardless of whether the exogenous or endogenous package sizes are used. In addition, market outcomes depend not only on the optimal pricing strategy but also on the optimal project target. Moreover, the creator can benefit from providing two types of packages instead of one type of package. Finally, the creator can strategically reduce the size of the large package and narrow the gap between the two packages to attract more funds.